2009
DOI: 10.1016/j.tox.2009.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and toxicity of green tea polyphenols in fasted and non-fasted dogs

Abstract: Standardized green tea extract was evaluated for exposure and toxicity in Beagle dogs following oral dosing by capsules. The main component (-)-epigallocatechin gallate (EGCG) accounted for 56-72% of the material. A 9-month chronic study (0, 200, 500, and 1000 mg/kg/day) was done in fasted dogs to take advantage of the reported improved catechin bioavailability with fasting. Extensive morbidity, mortality, and pathology of many major organs led to its early termination at 6.5 months and prevented identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 34 publications
3
77
1
2
Order By: Relevance
“…Plasma EGCG concentrations in mice tend to be closer to levels reported in human studies compared to levels in rats, in which administration of similar doses results in higher plasma concentrations [188]. Chronic toxicity studies in beagle dogs, showed 67% lethality within 26 weeks of daily doses of 200-800 mg/kg Polyphenon E, a pure and standardized green tea extract, when the dogs fasted for 20 h prior to EGCG administration [193]. However, replication of the 200-mg/kg dose for 13 weeks did not result in any deaths compared to the previous study, in which 3/8 deaths were recorded at that dose [193].…”
Section: Effects On Ttr Toxicity In Vivomentioning
confidence: 50%
See 1 more Smart Citation
“…Plasma EGCG concentrations in mice tend to be closer to levels reported in human studies compared to levels in rats, in which administration of similar doses results in higher plasma concentrations [188]. Chronic toxicity studies in beagle dogs, showed 67% lethality within 26 weeks of daily doses of 200-800 mg/kg Polyphenon E, a pure and standardized green tea extract, when the dogs fasted for 20 h prior to EGCG administration [193]. However, replication of the 200-mg/kg dose for 13 weeks did not result in any deaths compared to the previous study, in which 3/8 deaths were recorded at that dose [193].…”
Section: Effects On Ttr Toxicity In Vivomentioning
confidence: 50%
“…Chronic toxicity studies in beagle dogs, showed 67% lethality within 26 weeks of daily doses of 200-800 mg/kg Polyphenon E, a pure and standardized green tea extract, when the dogs fasted for 20 h prior to EGCG administration [193]. However, replication of the 200-mg/kg dose for 13 weeks did not result in any deaths compared to the previous study, in which 3/8 deaths were recorded at that dose [193]. Fasting dogs receiving a single dose of 120 mg/kg/day or 400 mg/kg/day died or were sacrificed due to their moribund condition starting at 7 weeks of a 13-week study [190].…”
Section: Effects On Ttr Toxicity In Vivomentioning
confidence: 99%
“…In-vitro studies have shown that EGCG is a low-affinity inhibitor of hERG, 26 but in-vivo studies in dogs could not relate these effects to cardiac toxicity. 27 Nevertheless, cardiac toxicity at high doses cannot be excluded and caution should be taken when EGCG is given concurrently with cardiovascular drugs. In our study, we did not see alterations in ECG during EGCG treatment.…”
Section: Discussionmentioning
confidence: 99%
“…EGCG adalah catechins yang paling umum dan paling aktif pada teh hijau dengan konsentrasi fisiologis 0,1-10 mikromolar. 8,[10][11][12] EGCG juga merupakan komponen utama teh hijau yang berperan pula dalam menghambat IL-2 yang bersumber dari sel T. Hambatan ini akan memberi efek pada fungsi IL-2 yang secara normal merespons sel B untuk mengeluarkan antibodi. Salah satu antibodi yang dihambat pengeluarannya adalah IgE sehingga akan mengurangi kadar IgE pada rinitis alergika.…”
Section: Pembahasanunclassified